Nationalism and Familyhood: the Struggle against Authoritarian Government as Seen in Leila Chudori’s Laut Bercerita - Antonius Wisnu Yoga Windharto (Indonesian Journal of English Language Studies (IJELS), 2018)
Social injustice is the reason why people protest against the government. The activists seek to find the equality from the government. As the result, some of activists were abducted and killed by the soldiers. The activists are not the group of people who hate the country. Most of them are nationalists, and they cannot keep silent in seeing the injustice in front of their eyes. The family of the activists also play important role in shaping the activists. The connection between the members of family is important in shaping their nationalism. Laut Bercerita is a novel which talks about nationalism and familyhood in Indonesia. Using this novel as the primary data, the issue of nationalism and familyhood as the characteristics of South East Asian people are discussed in this paper.